PENGARUH KEMISKINAN, PEMBANGUNAN MANUSIA DANDANA ZAKAT TERHADAP PERTUMBUHAN EKONOMI DIINDONESIA DAN MALAYSIA TAHUN 2011-2020 - Luthfiyyah Naurah Bayu (2022)
Economic growth is one of the indicators to reflect economic development run by a country. The movement of economic growth could be identified by the growth of the Gross Domestic Product (GDP) produced by that country. A country must be aims to reach a great and sustainable economic growth. This study aims to explain the effect of Poverty, Human Development and Zakat Fund on Indonesia and Malaysia Economic Growth 2011-2020. This study uses quantitative methods using secondary data. This research using panel data regression as analysis method tool. The result of this thesis showed that poverty, human development and zakat fund partially influence the economic growth. Also, simultaneously poverty, human development and zakat fund influance the economic growth.